The Use of Cooperative Learning Method, Volleyball Games to Improve Passing Results - Muhammad Ali (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2023)
This research aims to increase the use of cooperative learning in the game of volleyball in improving passing results in class VIII students at SMP Negeri 1 Lokop, East Aceh Regency. This research method is a survey with a questionnaire of 22 students. The instrument used to collect data in this research was a questionnaire content assessment sheet. Based on the results of research that has been carried out, it is known that the use of cooperative learning in volleyball games can improve passing in class VIII students at SMP Negeri 1 Lokop, East Aceh Regency. Where it can be seen that there has been an increase in students' passing results before and after implementing cooperative learning.